2015
DOI: 10.1111/hpb.12490
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of contralateral liver lobe hypertrophy after unilobar selective internal radiation therapy with Y90

Abstract: Background: Curative liver resection is the treatment of choice for both primary and secondary liver malignancies. However, an inadequate future liver remnant (FLR) frequently precludes successful sur-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
(22 reference statements)
1
26
0
1
Order By: Relevance
“…Currently, Y 90 microspheres may also be a reasonable alternative in patients who are potential candidates for resection but display a small FLR [14]. Although PVE is the gold-standard modality for inducing hypertrophy of the FLR [59], Garlipp et al [60] showed a lesser, but still pronounced, benefit of Y 90 particles with regard to contralateral liver hypertrophy after TARE. Moreover, TARE minimizes the risk of tumor progression in the treated lobe, possibly making it a suitable modality for selected patients.…”
Section: R0 Resection Is Compromised As a Results Of A Large Tumor Burmentioning
confidence: 99%
“…Currently, Y 90 microspheres may also be a reasonable alternative in patients who are potential candidates for resection but display a small FLR [14]. Although PVE is the gold-standard modality for inducing hypertrophy of the FLR [59], Garlipp et al [60] showed a lesser, but still pronounced, benefit of Y 90 particles with regard to contralateral liver hypertrophy after TARE. Moreover, TARE minimizes the risk of tumor progression in the treated lobe, possibly making it a suitable modality for selected patients.…”
Section: R0 Resection Is Compromised As a Results Of A Large Tumor Burmentioning
confidence: 99%
“…Preoperative identification of patients who had these poor predictor factors and hence were at high risk of early mortality after surgical resection would enable clinicians to better select and counsel patients for resection based on their individual risk‐benefit ratio for surgical resection. Presently, with the development of newer, less invasive treatments for HCC, such as Y‐90 SIRT, which has been shown to more effective than conventional TACE for large tumors , some of these patients could potentially benefit from a less aggressive treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the effects of SIRT on liver volume, several groups described an increase in volume of the contralateral lobe together with atrophy of the targeted lobe. [28][29][30] Analyzing the histopathological changes in the liver, we found liver atrophy after SIRT together with slight signs of hypertrophy in the non-targeted lobe. Despite the small number of patients in this sub-group, our findings support the clinical effects of SIRT on liver volume.…”
Section: Atrophy and Hypertrophymentioning
confidence: 90%